Soy Isoflavones Ameliorate the Adverse Effects of Chemotherapy in Children - Tacyildiz, Nurdan; Ozyoruk, Derya; Yavuz, Gulsan; Unal, Emel; Dincaslan, Handan; Dogu, Figen; Kucuk, Omer (Routledge Journals, Taylor & Francis Ltd, 2010)
Genistein sensitizes cancer cells to chemotherapy and radiation by modulating cell survival pathways. At the same time, genistein's antioxidant and anti-inflammatory effects may protect normal tissues from adverse effects of chemotherapy and radiation, which are largely due to oxygen-free radicals and inflammation. We conducted a small pilot study with a soy isoflavone mixture containing 8 mg of genistein in children receiving chemotherapy and/or radiation to investigate genistein's potential toxicity preventive effect. We monitored clinical and laboratory parameters in children with cancer who received their first cycle of chemotherapy without genistein and the subsequent cycles with genistein. Patients served as their own controls, and the clinical-laboratory data from the first cycle were compared to the data from subsequent cycles. Nine cycles of chemotherapy were administered without genistein and 57 cycles with genistein. Patients experienced less myelosuppression, mucositis, and infection when they received genistein with chemotherapy. During supplementation, serum genistein levels were 2 to 6 times higher compared to presupplementation levels. Patients who received abdominal radiation reported less pain and diarrhea when they took the genistein supplement. Further clinical investigation of soy isoflavones in pediatric cancer patients receiving chemotherapy and/or radiation should be conducted.
Keywords: Factor-Kappa-B; Prostate Carcinoma; Genistein; Radiation; Growth; Men; Angiogenesis; Inhibition; Stress